Impacts to agriculture and critical infrastructure in Argentina after ashfall from the 2011 eruption of the Cordón Caulle volcanic complex: An assessment of published damage and function thresholds - Craig, Heather (2016)
The 2011 Cordón Caulle (Chile) was a large silicic eruption that dispersed ashfall over 75,000 km2 of land in Central Argentina, affecting large parts of the Neuquén, Río Negro, and Chubut provinces, including the urban areas of Villa la Angostura, Bariloche and Jacobacci. These regions all received damage and disruption to critical infrastructure and agriculture due to the ashfall. We describe these impacts and classify them according to published damage/disruption states (DDS). DDS for infrastructure and agriculture were also assigned to each area using the tephra thickness thresholds suggested by previous studies reported in the volcanological literature. The objective of this study was to evaluate whether the impacts were as expected based on the DDS suggested thresholds, and to determine whether other factors, apart from ashfall thickness, played a part. DDS thresholds based on tephra thickness were a good predictor of the impacts that occurred in the semi-arid steppe area around Jacobacci. This was unexpected as the more severe impacts were related to the challenging environmental conditions (low precipitation levels, high levels of wind erosion) and the daily wind remobilisation of ash that occurred, rather than the ashfall thicknesses received. The temperate region, including Villa la Angostura and Bariloche, performed better than the DDS assigned by ashfall thickness suggested. Despite deposits as thick as 300 mm, full recovery occurred within months of the ashfall event. The DDS scales need to incorporate a wider range of system characteristics, and environmental and vulnerability factors, as we propose here.